Increase in human West Nile and Usutu virus infections, Austria, 2018 - Aberle, Stephan W. (Euro Surveill, 2018)
Between 28 June and 17 September 2018, 27 cases of human West Nile virus infections were recorded in Austria; four cases of West Nile neuroinvasive disease, 11 cases of West Nile fever, six infections detected by blood donation screening and six imported cases. In addition, 18 cases of human Usutu virus infections (all blood donors) were recorded. This is the highest number of annual infections recorded in Austria since the introduction of both viruses.